Management of Expressed Breast Milk as a Strategy to Optimize of Exclusive Breastfeeding - Nirmala Kusumaningrum Sunaryo; Elfi Quyumi Rahmawati (Universitas STRADA Indonesia, 2024)
Exclusive breastfeeding had many benefits for mothers and babies. Maternal employment was one of the factors that was closely related to the decline in exclusive breastfeeding coverage. Therefore, there was a need for education for mothers of toddlers to continue providing breast milk even though they were working. This community service program aimed to provide education to mothers of toddlers on how to manage expressed breast milk so that even though the mother was working, her child still received breast milk. The method used was to provide health education about the importance of exclusive breastfeeding and procedures for managing expressed breast milk. The number of Posyandu Balita participants was 123 toddlers and their mothers, but around 61 toddlers and their mothers actively participated in Posyandu. The demographic target for this community service activity is mothers of toddlers who were registered at Posyandu and were willing to take part in educational activities until completion, they were 30 mothers of toddlers. After being given education, an evaluation was carried out by giving questions to participants. Increased knowledge was known when participants were able to answer questions after conducting outreach activities. Before education process 85% of participants said that they did not understand and after education process 100% participants said that they understood.